Exploration for epithermal Au–Ag deposits in New Zealand: history and strategy. Issue 4 (2nd October 2019) - Christie, Anthony B.; Simpson, Mark P.; Barker, Richard G.; Brathwaite, Robert L.
ABSTRACT: More than 80 Cenozoic low sulphidation Au–Ag epithermal deposits and prospects are known in Northland, the Hauraki Goldfield (Coromandel Volcanic Zone) and the Taupō Volcanic Zone of the North Island. Reconnaissance exploration since the 1970s has included magnetic surveys, and stream sediment and rock-chip geochemical surveys. Prospect-scale exploration over the same period has included rock and soil geochemical surveys, magnetic and resistivity/induced polarisation geophysical surveys and drilling, including the study of hydrothermal alteration mineralogy (by thin section and XRD) plus fluid inclusion systematics, to help reconstruct the former hydrothermal system and identify zoning related to mineralisation. Since the 1990s, digital regional exploration and research data sets have enabled GIS-based targeting of prospective areas. At the prospect scale, multi-element ICP and ICP-MS analyses, hyperspectral short wave infrared spectral analyses and portable XRF geochemical analyses of field samples and drill core have been used to complement assay data for identifying spatial trends in geochemistry and mineralogy that help vector to mineral occurrences. Exploration since the 1970s has discovered new Au and Ag resources in extensions of some previously mined deposits (e.g. Golden Cross and Karangahake) and in new deposits in adjacent areas (e.g. Favona, Trio and Correnso in the Waihi area).